Bioenergetic Consequences of FLAG Tag Addition to the C-Terminus of Subunit 8 of Yeast Saccharomyces cerevisiae Mitochondrial ATP Synthase - I MADE ARTIKA (Bogor Agricultural University, Indonesia, 2010)
The yeast mitochondrial F1F0-ATP synthase is a multisubunit complex that contains at least 17 different subunits. Subunit 8 of yeast mitochondrial ATP synthase is a hydrophobic protein of 48 amino acids encoded by the mitochondrial ATP8 gene. Subunit 8 has three distinct domains; an N-terminal domain, a central hydrophobic domain and a C-terminal domain. FLAG tag addition to subunit 8 protein potentially facilitate elucidation of its topology, structure, and function. It has been shown that following incorporation of FLAG tag to its C-terminus, subunit 8 still assemble into functional ATP synthase complex. In order to analyze bioenergetic consequences of the FLAG tag addition, a yeast strain expressing FLAG tagged-subunit 8 was subjected to cellular respiration assays. Results obtained showed that addition of FLAG tag to the C-terminus of subunit 8 does not impair its proper functioning. The FLAG tag system, therefore, can be employed to study subunit 8’s detailed structure, topology, and function.